The Impact of Dehulling and Germination on the Physiochemical, Protein Solubility and Water and Oil Holding Capacities of Yellow Eye Bean (Phaseolus vulgaris L.) Protein Concentrates - Viana, Lauren; English, Marcia (Frontiers in Sustainable Food Systems, 2022)
Pulse varieties including Yellow Eye (YE) beans (Phaseolus vulgaris L.) are a rich source of protein (~26.5%) that can be utilized to create value-added protein concentrates. Pre-treatments including dehulling and germination have been shown to be effective at improving the nutritional and functional properties of extracted protein concentrates. However, the composition and functionality of these protein concentrates can vary depending on the pre-treatments and the method of extraction used (salt vs. alkaline). Furthermore, little is known about the impact of combining these different processing methods on the properties of YE bean protein concentrates. The objective of this study was to evaluate how germination and dehulling pre-treatments individually and when combined influence protein extraction efficiency, physiochemical properties (surface hydrophobicity and intrinsic fluorescence), and the functionality (solubility, oil and water holding capacities) of salt and alkaline extracted protein concentrates. Compared to the salt extracted concentrates, the alkaline protein concentrates exhibited higher protein recovery yields (16–23% vs. 43–56%) respectively. Conversely, the salt extracted protein concentrates exhibited superior functional properties as observed by improved water holding capacities and less variation in their solubilities at different pH values (4 to 10). When the pre-treatments were combined, the salt extracted concentrates exhibited improved extraction efficiencies and improved hydrophobicity and intrinsic fluorescence, whereas the opposite trend was observed in the alkaline protein concentrates. These observations were attributed to differences in the protein content and composition of the salt vs. alkaline protein concentrates. Overall, these findings suggest that dehulling and germination are potential processing methods that may be used to improve the physiochemical characteristics of salt extracted protein concentrates from yellow eye beans. Future research may investigate the potential application of these ingredients in different food formulations.